Economic and Social Consequences of Cancer in Kenya : Case Studies of Selected Households - Lehmann, Joel (World Bank, Washington, DC, 2020)
The burden of NCDs in Kenya is rising rapidly, and now accounts for more than 50 percent of all hospital admissions, and nearly 30 percent of total deaths. Cancer is the second leading cause of NCD mortality in Kenya, with the incidence of cancer nearly doubling between 2008-2012. The illness affects Kenyans of all ages and socio-economic backgrounds, with an increasing risk of cancer as age progresses. Most cancer cases are diagnosed at an advanced stage when treatment options are limited, leading to poor prognosis and high fatality rates. This report uses a case study approach with focus group discussions and in-depth interviews to shed light on the patient journey, and better understand the direct and indirect costs families face; the difficult decisions and choices they need to make; and the socio-economic and psychological implications of having a family member afflicted by cancer. Key challenges identified include lack of awareness and poor knowledge of cancer; late health seeking behavior; inadequate health insurance coverage and gaps in the benefit package which limit access to critical diagnostic tests, treatments and drugs; and socio-cultural barriers, including stigma, fear and myths that impede patients from seeking care early. The main themes from the patient stories and focus group discussions, including the economic impact on patients and households are summarized and a series of recommendations to mitigate the cost of cancer to patients and families are proposed based on the findings from the case studies.